Analysis of Factors Associated with Nutritional Status in School-Age Children at SD Negeri 10 Benteng Sidrap Regency - Nurhaedah, Nurhaedah; Fitri, Lidia; Asmy, Ulul (International Journal of Health Sciences, 2024)
Nutrition is very important in growth and development. Good nutritional status requires more attention because poor nutritional status in children will affect mental, physical growth or thinking abilities, of course, will reduce the level of productivity and ability in adulthood. The aim of this research is to determine the factors associated with the nutritional status of school- age children at SD Negeri 10 Benteng Sidrap Regency. Quantitative research method with a cross sectional study design. The sample consisted of 158 students at SD Negeri 10 Benteng. Data was collected using questionnaires and measurements of body weight and height. Data analysis used the Chi Square Test with a 95% confidence level. The results of this study show that there is a relationship between income with p value = 0.000, knowledge about nutrition with p value = 0.000, parents' education with p value = 0.000, parents' occupation with p value = 0.025, students' snack habits with p value = 0,000, with the student's nutritional status. The conclusion is that the factors that influence nutritional status are income, knowledge about nutritional status, parental education, parental occupation, parental characteristics and snack habits.